Pengaruh Peer To Peer Lender (P2P) Dan Payment Gateway Terhadap Kinerja UMKM Pada Masa Pandemi Covid-19 Dengan E-commerce Sebagai Variabel Moderating - Siti Maysaroh; Diansyah Diansyah (Business Management Journal, 2022)
This research is motivated by the fact that several MSME actors have started implementing or using peer to peer lenders, payment gateways and e-commerce in their business activities, especially in Johar Baru District, Central Jakarta. This study aims to determine the effect of peer-to-peer lenders and payment gateways on MSME performance during the Covid-19 pandemic using e-commerce as a moderating variable. Peer To Peer Lenders and Payment Gateways are independent variables and MSME performance is the dependent variable in this study. In this study there is a moderating variable, namely E-commerce. Data analysis method using SmartPLS. The population in this study is MSMEs located in Johar Baru District, Central Jakarta with a total sample of 150 MSMEs with purposive sampling method. The results showed that Peer To Peer Lenders had a significant positive effect on MSME Performance, Payment Gateway had a significant positive effect on MSME Performance, E-commerce had a significant positive effect on MSME Performance. Peer To Peer Lenders moderated by E-commerce have a significant positive effect on MSME performance. While the Payment Gateway moderated by E-commerce has a negative and significant impact on the performance of MSMEs. Keywords: Financial Technology, Peer To Peer Lenders, Payment Gateway, E-commerce. MSME performance.